Engineering students’ perception towards Malaysian nationhood course - Isa, Khairunesa; Wan Muda, Wan Hanim Nadrah; Ahmad, Abd. Rahman; Md. Yusoff, Rosman; Abd Kadir, Zulida (Science Publishing Corporation (SPC), 2018)
University students are among those who are responsible in setting the goals of national development. Therefore, they should possess good values in which portraying their personal identities, thus reflects the multiracial culture of Malaysia. However, a number of incidents such as the issue of National Anthem (Negaraku), AUKU conflicts, campus political extremes, gangsters’, conflict of identity and so on do ruin their images as the ones who are intellectuals. This condition leads to the question of students’ nationalism, particularly engineering students, where they are more concentrating on their technical courses compared to university requirement courses. This research was a survey designed research. The objectives of the research were (i) to determine the engineering students’ level of appreciation towards Malaysian Nationhood course, (ii) to determine students’ perception towards Malaysian Nationhood course, and (iii) to identify the students’ preferences on university courses. A total of 200 students were randomly selected as the respondents of the research. The frequencies and percentages were analyzed using descriptive analysis. Findings showed that the engineering students’ level of appreciation towards the Malaysian Nationhood course was at moderate level as they perceived the attendance to the course was mandatory. Almost students agreed that they would not enroll in the course if they were given the choice. Overall, it showed that the students attended the class as it was a compulsory course set by the ministry. The findings portrayed the students’ nationalism. Based on these findings, it is suggested that a more comprehensive modules and approaches which fulfill the needs of students should be prepared in order to emphasize the importance of nationalism among the students.